Urgensi City Branding Dalam Paradiplomasi : Studi Kasus Kabupaten Serang - Rizkiya Ayu Maulida, Rizky Hikmawan (Mandala: Jurnal Ilmu Hubungan Internasional, 2019)
In the era of globalization, regions is required to increase their capacity to meet the needs of the society. Unfortunately not all regions have advantages in their efforts to fulfill the welfare of its people. There are regions that do not have a significant level of income so the economic growth relatively slow. This situation need to be overcome by the local government by implementing specific strategies that are expected to be an alternative to increase the regional income. One of the strategy that can be taken by the local government is to carry out some cooperation with another actors from outside the country. The cooperation is expected to bring investment which can bring positive results for regional development, including the welfare of the people. However, before carrying out foreign cooperation, the local government must be able to form a regional branding which is expected to be a unique value for foreign parties to work together. In this article we try to provide input for the local government of Kabupaten Serang to form a special branding for the region. Through this research, we hope to help Kabupaten Serang to design strategic foreign cooperation and by the end produce many benefits for the society